The Foundation and Development of New Zealand Local Government: An Administrative Work in Progress - Andrew CARDOW (Transylvanian Review of Administrative Sciences, 2007)
From its genesis in Mid 19th Century liberalism to its current rationalist position, local government in New Zealand has followed a similar path to that of New Zealand central government in that it has embraced a neo liberal economic rationalist view of its role in public policy. The article traces the historical foundation of New Zealand local government and the factors that have assisted in forming the current shape of local government in New Zealand. The article ends by suggesting that the system of local government is dynamic and is still in development.